(untitled) (Journal of Research and Thought on Islamic Education (JRTIE), 2026)
This study aims to examine the implementation of the yellow book extracurricular program in improving students’ learning interest at Madrasah Aliyah Nurul Huda Wadeng and to identify the supporting and inhibiting factors in its implementation. This research employed a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation. The research subjects consisted of the head of the madrasah, supervising teachers, and students participating in the extracurricular program. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results show that the implementation of the yellow book extracurricular program is carried out systematically through components, including: objectives, time, place, participants, materials, and learning processes. The program applies several methods such as sorogan, bandongan, discussion, and question-and-answer. The findings indicate that the program contributes to improving students’ learning interest, as reflected in increased participation, attention, engagement, and confidence in learning activities. The supporting factors include institutional support, the role of supervising teachers, and students’ motivation. Meanwhile, the inhibiting factors consist of limited time allocation, differences in students’ abilities, and students’ physical fatigue after formal learning activities. In conclusion, the kitab kuning extracurricular program plays a significant role in enhancing students’ learning interest. Therefore, optimal management is needed through strengthening institutional support, improving teaching quality, and adjusting learning strategies to students’ conditions.